The antibody responses to adult-worm antigens of Schistosoma haematobium, among infected and resistant individuals from an endemic community in southern Ghana - Osada, Y.; Anyan, W.K.; Boamah, D.; Otchere, J.; Quartey, J.; Asigbee, J.R.; Bosompem, K.M.; Kojima, S.; Ohta, N. (Annals of Tropical Medicine and Parasitology, 2004)
Antibody responses to antigens from adult Schistosoma haematobium were investigated in an endemic community in Ghana, using microplate-ELISA. The results of a survey of egg output in urine and of a questionnaire-based investigation of water-contact activities were used to select 'endemic normal' (EN) and patently infected (PI) individuals as subjects. The plasma levels of antibodies reacting with the adult-worm antigens were determined and compared and the correlations between these levels and the age, water-contact index and egg output of each subject were evaluated. Compared with the EN subjects, the PI generally had higher levels of anti-worm IgG and IgE but lower levels of anti-worm IgA. When the data for the EN and PI groups were combined, the levels of anti-worm IgG and IgE were found to be positively correlated with egg output and with each other. Whichever the antibody class considered, levels of anti-worm antibodies were never negatively correlated with egg output. These results indicate that anti-worm IgE and IgG could be used as markers to reflect current infection intensity, and that anti-worm antibodies may not act as protective antibodies in the natural course of urinary schistosomiasis.